Serum ischemia modified albumin level in acute migraine attacks - Gurger, Mehtap; Gül, Evrim (My University, 2021)
Although the pathogenesis of migraines is not yet fully known, oxidative stress is thought to play an important role in the pathogenesis of this disease. In our study, we aimed to evaluate the serum level of ischemia-modified albumin (IMA), one of the systemic markers of oxidative stress, in acute migraine attacks admitted to the emergency department. The study included a control group consisting of 40 healthy individuals and a group of 40 patients admitted to the emergency department with migraine attacks. Serum IMA levels were studied using the ELISA kit. The average age of the migraine group was 39.9±8.2 and 31 were female. The average age of the control group was 42.5±9.2 and 29 were women. There was no difference between groups in terms of age and gender (p=0.18, p=0.79, respectively). Mean serum IMA levels were significantly higher in the migraine group than in the control group (p=0.001). On receiver operating characteristic curve (ROC) analysis, use of optimal IMA cutoff level of 92.6 ng/ml was associated with 70% sensitivity and 55% specificity (AUC= 0.713, 95% CI: 0.600-0.826, p= 0.001). In the migraine group the mean attack frequency was 2.55±1.3 within three months, with an average duration of migraine 8.87±4.76 years. The mean Visual Analogue Scale (VAS) was 8±1.2. A positive correlation was found between IMA levels and duration of migraine (r= 0.621, p= 0.001), attack frequency (r= 0.568, p = 0.001) and VAS (r= 0.352, p= 0.026). We found that serum IMA levels in acute migraine attacks were significantly higher than in the control group.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Klinik Nöroloji; Nörolojik Bilimler